Proton-driven plasma wakefield acceleration in AWAKE. (12th August 2019) - Gschwendtner, E.; Turner, M.; Adli, E.; Ahuja, A.; Apsimon, O.; Apsimon, R.; Bachmann, A.-M.; Batsch, F.; Bracco, C.; Braunmüller, F.; Burger, S.; Burt, G.; et al.
Abstract : In this article, we briefly summarize the experiments performed during the first run of the Advanced Wakefield Experiment, AWAKE, at CERN (European Organization for Nuclear Research). The final goal of AWAKE Run 1 (2013–2018) was to demonstrate that 10–20 MeV electrons can be accelerated to GeV energies in a plasma wakefield driven by a highly relativistic self-modulated proton bunch. We describe the experiment, outline the measurement concept and present first results. Last, we outline our plans for the future. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.